Multiple, disseminated cutaneous metastases of vulvar squamous cell carcinoma. Issue 2 (1st February 2004) - Ghaemmaghami, F.; Modares, M.; Behtash, N.; Moosavi, A. Z.
Abstract : Cutaneous metastases of vulvar carcinoma are extremely rare and have been reported in six patients so far. Our patient, who is the seventh one, is a 38-year-old woman with a history of diabetes mellitus. After detecting stage III squamous cell carcinoma of the vulva, she underwent radical vulvectomy and bilateral inguinal lymphadenectomy. She received 6000 cGy external beam radiation for positive margins. Six months later, she came back with multiple advanced skin lesions. Biopsy was performed and lesions were confirmed as cutaneous metastases. For her palliation, some chemotherapy drugs were prescribed. She is on her sixth chemotherapy cycle, but these skin lesions are somewhat a preterminal event and there is no well-established treatment for this phase of disease.